Comparison of Guy’s Stone Score and S.T.O.N.E. Nephrolithometry in Predicting Stone-Free Status After Mini-Percutaneous Nephrolithotomy - Akhtar, Muhammad Talha; Badar Murtaza; Ghufran Ahmed; Ammar Yasir; Muhammad Farooq Shahid; Asim Aslam (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare the performance of the Guy’s score and the S.T.O.N.E. score in predicting stone-free status (SFS) in Pakistani patients undergoing mini-percutaneous nephrolithotomy (mini-PCNL) including single and multiple tracts at a tertiary care hospital of Pakistan. Study Design: Prospective comparative study. Place and Duration of Study: Urology department of Armed Forces Institute of Urology, Rawalpindi, Pakistan, from Nov 2024 to May 2025. Methodology: Adults (18–80 years) with renal calculi on non-contrast CT-KUB undergoing mini-PCNL were enrolled. Demographics and CT parameters were recorded, and Guy’s Stone Score (GSS) and S.T.O.N.E. score were calculated. Stone-free status (SFS) was residual fragments ≤4 mm on postoperative day-1 X-ray KUB. Results: One hundred-and-ten patients, out of which 79(72.0%) were male, and the mean age was 42.6±11.3 years, underwent mini-PCNL. Lower-pole access was used in 89(81.0%) patients and double-J stents in all. Nephrostomy was placed in 20(18.2%) patients. SFS was achieved in 91(82.7%). Groups were similar in age, sex, creatinine, and laterality. Mean GSS and S.T.O.N.E. were lower in SFS (1.8±0.95 and 5.81±1.14 p<0.001) than non-SFS (3.2±1.03 and 7.11±1.79 p=0.002). GSS showed AUC 0.83 (95% CI 0.72–0.92) versus S.T.O.N.E. 0.72 (0.57–0.86), with a p value of 0.017. Conclusion: Our results show that both GSS and S.T.O.N.E. meaningfully stratify the likelihood of stone free status (SFS) after mini-PCNL however GSS can better predict SFS as compared to S.T.O.N.E score.